AN ANALYSIS OF PREDISPOSING, ENABLING, AND REINFORCING FACTORS IN PREVENTING THE TRANSMISSION OF PULMONARY TUBERCULOSIS DISEASE ON PATIENTS’ RELATIVES IN TULUNGAGUNG REGENCY - Chalies Diah Pratiwi; Sandu Siyoto; Indasah Indasah (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2017)
Tuberculosis (TB) is one of the major causes of death. In the report of Tuberculosis Global 2014 which was realeased by World Health Organization (WHO) stated that the incidence happened in Indonesia was 1 million new cases every year. The percentage of the cases in Indonesia is 10 percent from entire cases in the world, so as to be the most second cases country along with Tiongkok. The objective of this study is to know the effect of predisposing, enabling, and reinforcing factors towards the efforts in preventing the transmission of pulmonary TB diseases on patients’ relatives in Tulungagung regency.This study was non experimental quantitative research by using research design with Cross Sectional observation method. The samples this study were the relatives who have the most emotional closeness with the patient of pulmonary TB as much as 285 respondents. The data obtained through questionnaire then it was analyzed by using ordinal regression test. Based on the ordinal regression test which was conducted where ρ < 0,05, hence that there was the effect of gender on the prevention of pulmonary TB transmission in Tulungagung regency, the effect of educational level on the prevention of pulmonary TB transmission in Tulungagung regency, the effect of knowledge on the prevention of Pulmonary TB transmission in Tulungagung regency, the effect of dwelling density on the prevention of pulmonary TB transmission in Tulungagung regency and the effect of coaching officer on the prevention of Pulmonary TB transmission in Tulungagung regency. Improvement of guidance and quality of service in Pulmonary TB prevention program by involving the family is expected so the patient will do prevention effort to pulmonary tuberculosis disease to support local goverment effort in decreasing incidence of pulmonary TB generally and particularly maintain personal health to achieve health society which play an active role in national development.